2019
DOI: 10.5194/hess-23-4661-2019
|View full text |Cite
|
Sign up to set email alerts
|

Distinct stores and the routing of water in the deep critical zone of a snow-dominated volcanic catchment

Abstract: Abstract. This study combines major ion and isotope chemistry, age tracers, fracture density characterizations, and physical hydrology measurements to understand how the structure of the critical zone (CZ) influences its function, including water routing, storage, mean water residence times, and hydrologic response. In a high elevation rhyolitic tuff catchment in the Jemez River Basin Critical Zone Observatory (JRB-CZO) within the Valles Caldera National Preserve (VCNP) of northern New Mexico, a periodic preci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 76 publications
0
24
1
Order By: Relevance
“…Across larger river basins, Schaller and Fan () and Fan () challenged the commonly held view that catchments are closed systems, finding instead that many are regional groundwater importers or exporters. Similarly, multiple CZOs and other experimental sites operating at headwater scales have found that groundwater in fractured bedrock aquifers commonly contributes to streamflow (Brantley et al, ; Jin et al, ; Markovich, Dahlke, et al, ; McIntosh et al, ; Payn et al, ; White et al, ). Key to this discussion is the recent recognition that even at well‐studied sites, we are only beginning to detect that our “shallow views” on the hydrologic cycle may miss large fluxes of water or oversimplify our conceptual models of these systems.…”
Section: On the Importance Of Going Deepmentioning
confidence: 95%
See 3 more Smart Citations
“…Across larger river basins, Schaller and Fan () and Fan () challenged the commonly held view that catchments are closed systems, finding instead that many are regional groundwater importers or exporters. Similarly, multiple CZOs and other experimental sites operating at headwater scales have found that groundwater in fractured bedrock aquifers commonly contributes to streamflow (Brantley et al, ; Jin et al, ; Markovich, Dahlke, et al, ; McIntosh et al, ; Payn et al, ; White et al, ). Key to this discussion is the recent recognition that even at well‐studied sites, we are only beginning to detect that our “shallow views” on the hydrologic cycle may miss large fluxes of water or oversimplify our conceptual models of these systems.…”
Section: On the Importance Of Going Deepmentioning
confidence: 95%
“…There have been some advances in small borehole installation that have allowed for important discoveries related to residence time and active circulation depths in fractured rock systems (Gabrielli & McDonnell, ), but these generally extend to only 10 m or so. Additional deep well drilling and greater application of geophysical methods (e.g., White et al, ) are needed to provide spatial characterization of hydrostratigraphy down to 100–200 m. New 3‐D gridded datasets that make use of existing permeability data and data from a range of other sources are needed to improve modeling efforts at large scales. We need new tools to characterize deep flow paths as well as the vertical storage and release of deep groundwater. The stable isotopes of hydrogen and oxygen have been workhorse tracers in water studies for decades.…”
Section: Summary and Vision For Moving Forwardmentioning
confidence: 99%
See 2 more Smart Citations
“…A clear need exists to directly observe and more rigorously constrain the active circulation depth in mountain watersheds by measuring hydraulic conductivity ( K ) and groundwater‐flux‐dependent variables, such as age and temperature ( T ), at discrete levels in the subsurface sufficiently deep to penetrate the inactive zone. An increasing number of hillslope nested wells are being installed at Critical Zone Observatories and other research watersheds (e.g., Salve et al., 2012; Tokunaga et al., 2019; White et al., 2019), and these have provided important information on the flow at different depths within the active system and the relative importance of different subsurface water stores in streamflow generation. However, to date these lack sufficient depth and/or adequate groundwater‐flux‐dependent data collection and interpretation to permit direct, robust delineation of the active circulation depth.…”
Section: Introductionmentioning
confidence: 99%